Seasonal co-pollution characteristics of parent-PAHs and alkylated-PAHs in karst mining area soil of Guizhou, Southwest China - An, Xianjin; Li, Wei; Lan, Jiacheng; Di, Xinyue; Adnan, Muhammad (Frontiers in Environmental Science, 2022)
The research on polycyclic aromatic hydrocarbons (PAHs) in karst soil mainly focuses on 16 kinds of parent-PAHs (p- PAHs), and little attention is given to alkylated-PAHs (a-PAHs) with higher concentration and greater toxicity. Five surface soils of coal mining area and their surrounding areas in karst area were sampled as subject investigated, and the spatiotemporal pollution characteristics of p-PAHs and a-PAHs were analyzed to discuss the impact of karst soil properties and environmental conditions on the migration of a-PAHs. The research results showed that the pollution concentration of a-PAHs in the soil of the southwestern karst area, especially the coal mining area, was significantly higher compared to the 16 kinds of p-PAHs, and the average concentration of the p-PAHs was 177.29 ± 37.36 ng/g; the concentration of a-PAHs was 346.87 ± 104.91 ng/g; the concentration of PAHs presented a seasonal pattern of that in winter>spring>autumn>summer. At the same time, seasonal rainfall could affect and change the occurrence state of PAHs in karst soils, but the effect on p-PAHs was weaker than on a-PAHs. The concentration of PAHs in the coal mining area and forest soil were 651.68 ng/g and 755.38 ng/g, respectively, so they belonged to contaminated soil, while the concentrations of two cultivated soil and abandoned soil are 475.51 ng/g, 367.58 ng/g and 370.63 ng/g, respectively, belonging to weakly contaminated. Toxicity assessment showed that p-BaP with a maximum toxic equivalent of 62.35 ng/g, C1-BaP (42.09 ng/g), DaA (37.82 ng/g) and C1-3 BaA (25.91 ng/g) were toxic PAHs with higher risk. The results of the correlation study showed that soil organic carbon, soil clay and soil calcium content were the dominant factors affecting the spatiotemporal distribution of PAHs of soils in karst coal mining areas and their surrounding areas. The research can provide data guidance for the management, control and restoration of soil pollution in karst areas, and offer a reference for Guizhou province to implement the big-ecological strategy.